Evaluating the effects of peer localization on a BitTorrent-based P2P video-on-demand network - Quevedo, Gene Paul L.
Video-on-demand (VoD) is a rapidly growing method for viewing and sharing video content over the Internet. However, video on demand consumes a significant amount of bandwidth, forcing content publishers and content delivery networks to examine approaches such as the use of peer-to-peer (P2P) technologies to assist in video distribution. We study the performance impact of a peer localization strategy aimed at limiting traffic exchanges between two autonomous systems such as Internet service providers (ISPs) in a P2P VoD setup. We performed our experiments using an emulated network and a modified BitTorrent client and tracker, with Debian OS virtual machines for increasing the scale of the system using Xen virtualization. Our findings suggest that peer localization can improve streaming performance while reducing network traffic crossing autonomous systems, potentially benefiting both users and providers, respectively. We have also made experiments using our hybrid approach in peer localization. Though this hybrid approach did introduce additional inter-domain traffic, it attained a download performance that is at par or slightly better to a fully localized P2P network, while at the same time, further reducing the total data uploaded by the original server of the video content.